Learning evidence based practice through involvement in investigation actiities: - CARDOSO, MÁRIO; Baixinho, Cristina Lavareda; Ferreira, Óscar Manuel Ramos; Nascimento, Patricia; Pedrosa, Ana Rita; Gonçalves, Paulo (Departamento de Enfermagem da Universidade Federal do Paraná, 2021)
Objective: to understand how students perceive their involvement in investigation activities and how they contribute for the development of evidence-based practices. Method: qualitative, cross-sectional, descriptive, and exploratory study, carried out in Portugal, in August 2019. A focus group of eight participants was formed to answer the question: “What are the advantages of the participation of nursing students in investigations for the development of knowledge, attitudes, and performance in the use of evidence?” The software NVivo was used for a content analysis. Results: five categories and subcategories emerged from the qualitative analysis of findings: selflearning, integration of theory and practice, interdisciplinary work, evidence-based decision making, and scientific literacy. Conclusion: creating an effective learning experience helps building knowledge and can contribute for the health of the community, for improved educational results during the internship, and for the development of the abilities necessary for Evidence Based Practice.
the self-perception of students
Keywords: Prática Clínica Baseada em Evidências; Aprendizagem; Estudantes; Enfermagem; Gestão do Conhecimento